Agri-Food Markets towards Agroecology: Tensions and Compromises Faced by Small-Scale Farmers in Brazil and Chile - Estevan Felipe Pizarro Muñoz (Sustainability, 2021)
One of the main dilemmas faced by small-scale farmers’ movements advocating for agroecology in Latin America lies in the trade-offs between the economic opportunities arising from the organic food market expansion, and the political principles at the core of their action. To provide insights on this issue, a survey was performed in Brazil and Chile. Between March 2016 and December 2018, data were collected through direct and participant observation, documentary analysis, and interviews conducted to peasant organizations’ leaders, technicians and policymakers. In Brazil, the research focused on the Movimento dos Trabalhadores Rurais Sem Terra (The Landless Movement); while in Chile, due to the absence of such a national social movement, it considered a wider set of actors, including the Instituto Nacional de Desarrollo Agropecuario (National Institute for Agricultural Development). The results show how social movements are navigating between the mainstreaming pressures of the conventional markets, dominated by the leading agri-food corporations, and the political efforts they have been doing to build civic food markets as alternatives to conventionalization patterns. Finally, we argue that social scientists should better explain the tensions and compromises the social movements go through in order to coordinate different and complementary marketing strategies.